Measurement of the charge asymmetry in highly boosted top-quark pair production in √s = 8 TeV pp collision data collected by the ATLAS experiment - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Physics letters, 2016)
In the pp→tt¯ process the angular distributions of top and anti-top quarks are expected to present a subtle difference, which could be enhanced by processes not included in the Standard Model. This Letter presents a measurement of the charge asymmetry in events where the top-quark pair is produced with a large invariant mass. The analysis is performed on 20.3 fb−1 of pp collision data at s=8TeV collected by the ATLAS experiment at the LHC, using reconstruction techniques specifically designed for the decay topology of highly boosted top quarks. The charge asymmetry in a fiducial region with large invariant mass of the top-quark pair (mtt¯>0.75 TeV) and an absolute rapidity difference of the top and anti-top quark candidates within −2<|yt|−|yt¯|<2 is measured to be 4.2±3.2%, in agreement with the Standard Model prediction at next-to-leading order. A differential measurement in three tt¯ mass bins is also presented.